A new color morph of Calappa flammea (Herbst, 1794), with implications for the taxonomy of Calappa Weber, 1795 (Decapoda: Brachyura: Calappidae). Issue 3 (18th July 2021) - Vossgaetter, Lennart; Larson, Paul; Macrander, Jason
Abstract: Many species of the brachyuran crabs in the family Calappidae, commonly known as 'box crabs' or 'shame-faced crabs, ' look alike and are difficult to distinguish at various developmental stages based on morphology alone. Some crabs recently collected as a part of the South East Atlantic Monitoring and Assessment Program (SEAMAP) groundfish surveys were identified as likely members of Calappidae, but could not be determined to species due to their unusual color pattern and size. The use of molecular data in combination with morphometrics suggests that the crabs in question belonged to Calappa flammea (Herbst, 1794). The specimens represent an undescribed unique color morph that deviates from their previous description and should be considered for future identifications. Several ecological factors can cause such color variations in crabs, but further investigation is needed to understand the drivers of the described phenotypic variance in C. flammea.